Os nomes de Arthur Bispo do Rosário - Maschio, Bruno (2020)
This work is a study around the most different Names of Bispo do Rosário and the ways in which these names are operators of the most distinct regimes of truth possible. From that point on, it was made an analysis of discourse, a study about the enunciation that takes Bispo do Rosário as an object to make him a subject, initially as Mad and thereafter as an Artist. But also a study of Bispo do Rosário's own enunciation, found in his works and sayings, especially around the questions that emerge from the particular use he does of Jesus Christ's name. It was searched to articulate how it was possible the attribution of identities of Artist and Mad to a subject that always stated he was Christ himself. The text divides into two distinct moments. The first part, "as experiências críticas" of Arthut Bispo do Rosário, focus on the production of identities, subjects, names, classification and categories. Such choice was made on the objective to chart the forces at play in the formation of identities and its molds, around the life and production of Arthur Bispo do Rosário, seeking to comprehend the limits and boundaries woven, time by the psychiatric rational, time by the artistic territory. In the second part, "RECONHECERAM - O FILHO DO HOME", there's as shifting, where the focus goes to the singularity of the work and enunciation of Arthur Bispo do Rosário. Throughout his life he would position himself as a divine envoy. He had the task of creating a catalog of the world to be presented to God on doomsday. His works, his life, are expressions of this mission: order the world. The text gets concluded with the use Bispo do Rosário does of Christ's name and the changes that are produced by such identification. More than proposing a commentary or an analysis, its adopted a perspectivist thesis. The matter becomes radically distinct: what happens in the world when we take seriously the enunciation of Other?